An Analysis of Autopsied Maternal Deaths in Dakshina Karnataka District Over A 10-Year Period - Nimisha Ratra 1 , Haneil Larson Dsouza2 , Pavanchand Shetty2 , B Suresh Kumar Shetty 3 , Jagadish Ra (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Though all deaths are accompanied by profound sorrow and anguish, maternal deaths are perhaps more so. Unfortunately, when these deaths are reported as medico-legal cases, the agony is then prolonged. Anguish from the family members is understandable, but opportunities to conduct autopsies on these deaths present an opportunity to examine in detail the pathophysiology of these deaths. This study is an attempt to find the cause of death in autopsied maternal death cases that have been filed as medico-legal cases and to compare the trends of autopsied maternal deaths with other regions. Objectives: To find the cause of death in autopsied maternal death cases that have been filed as medico-legal cases and to compare the trends of autopsied maternal deaths with other regions. Methods: A record-based study was conducted consisting of maternal deaths in the past 10 years based on the medico-legal autopsied reports from Government Wenlock Hospital mortuary. Results: Among the causes of death attributed, the most common cause of death was embolism related with 4 deaths. This included deaths due to amniotic fluid embolism, trophoblast embolism and their complications such as DIC. Haemorrhage was the cause of death in 2 cases. In 2 cases, the cause of death was acute liver failure. However, one of these cases also had features of gestational acute respiratory distress syndrome. In one case, the cause of death was attributed to coronary artery disease complicated by pregnancy. One case was of ruptured ectopic pregnancy. In another case, the cause of death was a surgical complication of a dilatation and curettage procedure. In the remaining 3 cases, the cause of death could not be ascertained even after histopathological examination, chemical analysis, and a complete autopsy.